EVALUATION OF WATER POTENTIAL IN CENTRAL ASIA IN THE CONTEXT OF THE TERM INTERESTS OF KAZAKHSTAN - A. Y. Bimenova (Проблемы постсоветского пространства)
In this article the problems of the Central Asian region in the use of transboundary water resources, their ways of solving a rational approach for each Central Asian country. Often the cause of current conflicts over water see planted in the Soviet era economic system. Such an approach is simplistic. In this paper, we propose a broader perspective on the causes of modern water disputes.